2016
DOI: 10.1259/bjr.20150536
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic mucinous cystoadenomas and cystoadenocarcinomas: differential diagnosis by means of MRI

Abstract: Objective: To determine the accuracy of MRI in differentiating mucinous cystoadenomas (MCAs) from mucinous cystoadenocarcinomas (MCACs) of the pancreas, with histopathological analysis as the reference standard, for better surgical planning. Methods: A total of 65 patients with histopathologically proven mucinous cystic neoplasms (MCNs) underwent MRI and surgery. Quantitative image analysis included size, septa and wall thickness and number of loculations. Qualitative image analysis included nodules; hyperinte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
6
0
1
Order By: Relevance
“…Studies have drawn different conclusions regarding the specific threshold value of cyst diameter over which the risk of malignancy is increased. It is generally believed that the cyst wall diameter in malignant MCN is usually > 4 cm[ 15 ], or that a diameter of ≥ 6 cm is a risk factor for malignant tumors[ 11 , 16 , 17 ]. In addition, other manifestations suggestive of malignant MCA include peripheral calcification, irregularly contoured cyst walls, thickening of internal septations, increased papillary projections, intracystic nodules, local organ invasion, and vascular obstruction and compression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have drawn different conclusions regarding the specific threshold value of cyst diameter over which the risk of malignancy is increased. It is generally believed that the cyst wall diameter in malignant MCN is usually > 4 cm[ 15 ], or that a diameter of ≥ 6 cm is a risk factor for malignant tumors[ 11 , 16 , 17 ]. In addition, other manifestations suggestive of malignant MCA include peripheral calcification, irregularly contoured cyst walls, thickening of internal septations, increased papillary projections, intracystic nodules, local organ invasion, and vascular obstruction and compression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other manifestations suggestive of malignant MCA include peripheral calcification, irregularly contoured cyst walls, thickening of internal septations, increased papillary projections, intracystic nodules, local organ invasion, and vascular obstruction and compression. Di Paola et al[ 16 ] studied 65 patients with MCNs who underwent magnetic resonance imaging and found that there may be a risk of malignant transformation if the diameter is greater than 7 cm, septa and wall thickness was > 3 mm, and there were nodules. In this study, the median diameter of MCA was 3.5 cm and that of MCC was 5.8 cm.…”
Section: Discussionmentioning
confidence: 99%
“…15,49,51 On imaging studies, larger cyst size, thickening of the septations within an MCN, and presence of an intracystic or adjacent solid mass are radiologic features that may suggest an associated invasive PDAC. 15,50,52 The cytopathologic features that are worrisome for invasive carcinoma arising from an MCN are similar to those for IPMN: nucleomegaly, clumped and irregular chromatin distribution, irregular nuclear contours, and crowding.…”
Section: Mucinous Cystic Neoplasmmentioning
confidence: 94%
“…Возраст пациента является значимым фактором увеличения риска развития карциномы из MCN [32]. Кроме того, независимыми факторами, увеличивающими риск малигнизации являются размер, толщина стенки и наличие внутрикистозного солидного компонента [38][39][40] Так же, как и IPMN, MCN гистологически делится на три типа в зависимости от тяжести диспластических изменений: I -MCN c дисплазией легкой или умеренной степени; II -MCN c дисплазией высокой степени (по сути рак in situ); III -MCN, ассоциированная с инвазивной карциномой [27].…”
Section: Mcnunclassified